Nurse’s Role in Caring for Mothers with Preterm Infants:Transition Phases of Motherhood - Jatulajanyalate, Netsumol (Journal of Nursing, Siam University, 2022)
Preterm labor is an unexpected experience and can negatively affect mothers as well as their babies. Premature babies are at higher risk of having health issues such as dyspnea, low birth weight, and congenital abnormalities. As a result, these babies have to be taken care of by the Neonatal Intensive Care Unit (NICU) and stay in a hospital longer than usual. Mothers will be separated from their babies immediately after giving birth and their roles as mothers will be limited under the context of clinical and infant health issues. This situation creates concern and difficulty during the transitional stage to the role of motherhood. Moreover, mothers tend to have issues in baby caring and mental health in a long term. Therefore, nurses should prioritize taking care of mothers with preterm labor in terms of providing awareness of mental issues, supporting empowerment concerning the role of motherhood, and discharge planning with families, as well as continuous monitoring with families and the development of communication channels. This will support mothers to be confident in taking care of babies and be able to overcome obstacles in order to complete their transition to the role of motherhood